When crystals become dust: Speleothem degradation processes in Praileaitz I Cave (Northern Spain) - Vadillo-Pérez, Iñaki; Aranburu, Arantxa; Iriarte, Eneko; Arriolabengoa, Martín; Berreteaga, Ana; Damas, L.; García, Patxi (My University, 2014)
Within the Praileaitz cave there are evident signs of deterioration of different types and generations, affecting both the host rock and the speleothems. The supports of many of the paintings, specifically the drapes, are in a clear state of deterioration due to disintegration of the texture of the speleothem, resulting from selective dissolution of the crystals and the creation of intercrystalline porosity. To analyse and study the different types of degradation and their causes, we gathered a total of 14 samples of speleothems and rock throughout the cave. The speleothems sampled are of different types and come from different growth phases. In order to monitor the parameters that may be causing the pathologies of degradation, a protocol was drawn up for measuring the environmental parameters and the condensation water and drip water in the cave. To analyse the water from the cave, samples were taken at four representative drip points in the cave and from condensation water.
Keywords: Espeleotemas; Caves; Speleothem; Degradation